2014
DOI: 10.5732/cjc.013.10139
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in women with cervical precursor lesions and cancer: a prospective, 6-month, hospital-based study in China

Abstract: The overall survival of patients with cervical cancer has improved due to detection at an early stage and availability of comprehensive treatments in China. As patients' lives prolonged, it is important to understand their health-related quality of life (QoL) during and after treatment. We used the EQ-5D questionnaire to assess QoL of 194 patients with cervical lesions at Sichuan University West China Second Hospital between May 2010 and January 2011. Patients were surveyed before primary treatment and at 1, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
4
25
1
Order By: Relevance
“…Toxicity classified as grade 3 or higher was considered severe. The irradiation-related adverse effects included bone marrow suppression, gastrointestinal reactions, irradiation-related enteritis, intestinal obstruction, intestinal fistula, irradiation-related cystitis, and urinary fistula [ 7 , 9 , 13 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxicity classified as grade 3 or higher was considered severe. The irradiation-related adverse effects included bone marrow suppression, gastrointestinal reactions, irradiation-related enteritis, intestinal obstruction, intestinal fistula, irradiation-related cystitis, and urinary fistula [ 7 , 9 , 13 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The 5-year survival rate of patients with stage II or III disease who receive concurrent chemoradiotherapy ranged from 53% to 74%; however, the 5-year survival rate of patients with stage IV disease was only 20% to 30% [ 5 ]. Different treatment algorithms affect surviving women to varying degrees, and radiotherapy is associated with longer-term adverse effects than surgery or chemotherapy [ 6 , 7 ]. Several studies have shown that adding brachytherapy to the treatment protocol results in prolonged survival for patients with cervical cancer [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In all patients, the positive changes in the index value and EQ VAS also coincided with other studies. A prospective study of Chinese patients with CIN conducted by Zhao and colleagues found that EQ-5D scores 1 month after treatment were signi cantly better than at baseline [6]. Therefore, we considered that post-surgical changes to patients' health can be qualitatively judged by the change in EQ-5D-5L score.…”
Section: Discussionmentioning
confidence: 99%
“…In all patients, the positive changes in UI and EQ VAS were also found in other studies. A prospective study in Chinese CIN patients conducted by Zhao et al expressed that the EQ-5D scores of 1 month after treatment was significantly better than the baseline [31]. Therefore, we considered that changes in health of CIN patients caused by surgical treatment can be qualitatively judged by the score change of the EQ-5D-5L.…”
Section: Discussionmentioning
confidence: 99%
“…The good news is that surgical treatment is a definitive treatment for CIN, and the cure rate is very high [5], so it as an effective measure to prevent the occurrence of invasive cervical cancer. Along with health-related quality of life (HRQoL) is increasing being concerned, patient-reported outcomes (PROs) are clinical endpoints other than survival, such as the EuroQol five-dimensional questionnaire (EQ-5D) [6].…”
Section: Introductionmentioning
confidence: 99%